Two‐scale ion meandering caused by the polarization electric field during asymmetric reconnection. Issue 15 (13th August 2016) - Wang, Shan; Chen, Li‐Jen; Hesse, Michael; Bessho, Naoki; Gershman, Daniel J.; Dorelli, John; Giles, Barbara; Torbert, Roy B.; Pollock, Craig J.; Strangeway, Robert; Ergun, Robert E.; Burch, James L.; et al.
Abstract: Ion velocity distribution functions (VDFs) from a particle‐in‐cell simulation of asymmetric reconnection are investigated to reveal a two‐scale structure of the ion diffusion region (IDR). Ions bouncing in the inner IDR are trapped mainly by the electric field normal to the current sheet ( N direction), while those reaching the outer IDR are turned back mainly by the magnetic force. The resulting inner layer VDFs have counter‐streaming populations along N with decreasing counter‐streaming speeds away from the midplane while maintaining the out‐of‐plane speed, and the outer layer VDFs exhibit crescent shapes toward the out‐of‐plane direction. Observations of the above VDF features and the normal electric fields provide evidence for the two‐scale meandering motion. Key Points: Ions have two scales of meandering motion close to the X line, dominantly trapped by the electric and magnetic force, respectively Ion distributions exhibit counter‐streaming beams and crescent shapes in inner and outer scales, leading to separate nongyrotropy peaks Counter‐streaming and crescent ion distributions are observed by MMS in magnetopause reconnection diffusion regions